MODEL PENINGKATAN KINERJA KARYAWAN MELALUI PERAN KOMUNIKASI DAN MOTIVASI SERTA PENGARUHNYA TERHADAP KEPUASAN KERJA - Abdul Hakim; Wuryanto . (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2014)
The aim of this research was to analyse and receive proof emperis the influence of communication and the work motivation on job satisfaction and the achievement of the employee of the Alam Baru Furniture Company. The problem that was promoted in this research was 1) Whether having the influence of communication on the employee’s job satisfaction of the Alam Baru Furniture Company? 2) Whether having the influence of the motivation on the employee’s job satisfaction of the Alam Baru Furniture Company? 3) Whether having the influence of communication on the achievement of the employee of the Alam Baru Furniture Company?4) Whether having the influence of the motivation on the achievement of the employee of the Alam Baru Furniture Company? 5) Whether having the influence of job satisfaction on the achievement of the employee of the Alam Baru Furniture Company?This research was carried out against the employee in the Nature company of Baru Furniture Jepara. The data collection was carried out with the questionnaire and the study of the book with the number of samples totalling 175 respondents that 112 female respondents and 63 male respondents. Technically the analysis of the data that was used was with Structural Equation Model (SEM) by using theAMOS program 16,0 because of enabling the combination between the analysis of the factor and the analysis of multiplied regression.Results of the research showed that the communication variable and the influential motivation in a signifkan manner towards job satisfaction. Moreover, communication and the motivation were influential towards the achievement of the employee in the Baru Furniture Jepara. Nature company, this could be proven by seeing the value probability the significance was smaller than standart 0.05.Key word : communication, motivation, job satisfaction, and achievement of the employee